Structure of Financial Position Report in Accordance with International Standards and its Comparison with NAS - Misirov, A.M.; Khodjimamadov, Sh.R. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
This article looks at how financial position reporting practices have grown in Uzbekistan. It compares national accounting standards (NAS) to international standards (IFRS). The study shows why it's key to bring Uzbekistan's financial reporting in line with global practices. This has an impact on making enterprises more stable and helps to make better decisions. The article breaks down the layout and setup of balance sheets under both NAS and IFRS. It points out main differences in how assets and liabilities are shown when it comes to liquidity. The research reveals how these differences change how clear and comparable financial results are. It gives insights on how using international standards can boost financial openness. The article stresses that financial statements and accounting records are vital to check a company's financial standing. They allow for good analysis of changes, performance comparisons, and benchmarking. In the end, bringing financial reporting in line with international standards is crucial to draw in foreign investment and ensure lasting economic growth in Uzbekistan.